Non-steroidal anti-inflammatory drug modulates oxidative stress and calcium ion levels in the neutrophils of patients with primary dysmenorrhea - Kaplan, Önder; Nazıroğlu, Mustafa; Güney, Mehmet; Aykur, Mehmet (Journal of reproductive immunology, 2013)
Primary dysmenorrhea is a common inflammatory disease with an uncertain pathogenesis, although one consistent finding is increased neutrophil activity. We aimed to investigate the effects of a non-steroidal anti-inflammatory drug (NSAID) on oxidative stress and Ca2+ levels in neutrophils from patients with primary dysmenorrhea. Blood samples were obtained for neutrophil isolation from six female patients with primary dysmenorrhea (patients) and six healthy female subjects. The NSAID (diclofenac) was taken daily by the patient group for 6 weeks before a second blood sample was taken. Neutrophils isolated after diclofenac treatment were investigated in three settings: (1) after incubation with verapamil and diltiazem (V+D), (2) after incubation with 2-aminoethoxydiphenyl borate (2-APB), and (3) with neither exposure. Neutrophil lipid peroxidation and stimulated intracellular Ca2+ levels were higher in the patients than in the controls, although their levels were reduced after six weeks of treatment with diclofenac. Ca2+ levels from neutrophils obtained after diclofenac treatment were further decreased after incubation with V+D or 2-APB, compared with those exposed to neither agent. Neutrophil glutathione peroxidase and total antioxidant status were lower in the patients than in the controls and higher post-treatment with diclofenac. Reduced glutathione levels were similar in the control, patient, and treatment groups. In conclusion, we observed the importance of Ca2+ influx into the neutrophils and oxidative stress in the pathogenesis of the patients with primary dysmenorrhea. The NSAID diclofenac appeared to provide a protective effect against oxidative stress and Ca2+ entry through modulation of neutrophil VGCC and TRP calcium channels.